The new East's new businesses: Heart of the labor market problem and/or part of the solution? - Kenneth Roberts; Colette Fagan; J. Tholen; Ladislav Macháček; Sijka Kovačeva; Bohdan H. Jung; A. Kurzynowski; T. Szumlicz; Klára Fóti (Journal for East European Management Studies, 2000)
This paper is based on evidence from interviews in 1997 with 400 young (aged up to 30) self-employed people, and parallel studies of the support being offered to the self-employed by state services and non-governmental organisations (NGOS), in four East-Central European countries (Bulgaria, Hungary, Poland and Slovakia). The samples represent the New East's better-established young business people. The evidence presented in this paper explains why, in turn-ofthe- century conditions, the New East's new businesses are in danger of becoming locked into low-productivity, low wage niches. It is argued that the prospects of the new market economies in the twenty-first century depend largely on the ways in which their relationships with the European Union develop, and forms of assistance that will promote the development of the more capable SMEs into quality businesses are identified: e.g. encouraging inward investors to become mentors and customers of local enterprises; encouraging banks to become small business-user-friendly; conglomerating assistance to small enterprises within regional support centres. – – Mit Hilfe der Daten, die in dieser Arbeit präsentiert werden, wird erklärt, warum die neuen Unternehmen des neuen Ostens Gefahr laufen, in eine Nische der niedrigen Produktivität und des Niedriglohns zu geraten. Die Aussichten der neuen Marktwirtschaften im 21. Jahrhundert hängen von der Entwicklung der Beziehungen zur EU ab. Es werden Formen der Unterstützung vorgestellt, mit deren Hilfe fähigere kleine und mittlere Unternehmen entstehen können: z. B.: Ermutigung von Investoren, auch Mentorenrollen zu übernehmen und Kunden lokaler Unternehmen zu werden; Ermutigung der Banken, kleinen Unternehmen gegenüber offen zu sein; Konzentration der Unterstützung in regionalen Support Zentren.
Keywords: 650